Identification of hsa_circRNA_100632 as a novel molecular biomarker for fulminant type 1 diabetes - Yin, Wenfeng; Luo, Shuoming; Qiu, Junlin; Xiao, Zilin; Zhang, Ziwei; Xie, Zhiguo; Li, Xia; Zhou, Zhiguang (Frontiers in Immunology, 2023)
Objective: Circular RNAs (circRNAs) are associated with diabetes, but their role in fulminant type 1 diabetes (FT1D) is unclear. Thus, we characterized the role of circRNAs in FT1D. Research Design and Methods: CircRNA expression profiles were detected in peripheral blood mononuclear cells (PBMCs) of five FT1D patients and five controls using a circRNA microarray. An independent cohort comprised of 40 FT1D cases, 75 type 1 diabetes (T1D) cases, and 115 controls was used to verify the circRNAs using quantitative real-time polymerase chain reaction (qRT-PCR). Spearman’s correlation analysis and receiver operating characteristic (ROC) curve analysis were performed to determine the clinical diagnostic capability of circRNAs. Bioinformatics was used to identify potential biological functions and circRNA–miRNA–mRNA interactions. Results: There were 13 upregulated and 13 downregulated circRNAs in PBMCs of patients with FT1D. Five circRNAs were further verified in a second cohort. Hsa_circRNA_100632 was significantly upregulated in the FT1D and T1D groups. Hsa_circRNA_100632 was differentiated between patients with FT1D and controls [area under the curve (AUC) 0.846; 95% CI 0.776–0.916; P＜0.0001] as well as between patients with FT1D and patients with T1D (AUC 0.726; 95% CI 0.633–0.820; P＜0.0001). Bioinformatics analysis showed that hsa_circRNA_100632 may be involved in 47 circRNA–miRNA–mRNA signaling pathways associated with diabetes. Conclusions: CircRNAs were aberrantly expressed in PBMCs of patients with FT1D, and hsa_circRNA_100632 may be a diagnostic marker of FT1D.